Features of energy transport in EuMgB₅O₁₀ and EuP₃O₉ quasi-one-dimensional lattices - Kononets, N.V.; Seminko, V.V.; Maksimchuk, P.O.; Bespalova, I.I.; Masalov, A.A.; Malyukin, Yu.V. (Functional Materials, 2014)
Processes of excitation energy migration in EuMgB₅O₁₀ and EuP₃O₉ quasi-one-dimensional matrices have been investigated by means of steady-state and time-resolved luminescence spectroscopy. It was shown that the patterns of energy migration in these materials are sufficiently different - while for EuMgB₅O₁₀ the most effective energy transport takes place at room temperature via ⁵D₀ →⁷F₁ transitions of Eu³⁺ ion, for EuP₃O₉ energy transfer is more effective at low temperatures and mediated by Eu³⁺-O²⁻ charge transfer states. The difference in energy transport processes can be explained taking into account the peculiarities of phonon subsystem for borate and phosphate matrices.